Narrative identities : psychologists engaged in self-construction - Yancy, George; Hadley, Susan (Susan Joan), 1967- (Jessica Kingsley Publishers, 2005)
'What a fascinating and illuminating work! Yancy and Hadley have succeeded in stimulating a group of accomplished narratologists in psychology ... to deliberate on the ways in which their life experiences are related to their scholarly explorations of narrative. The authors ... grace us with illuminating and articulate insights into the close linkages between personal and intellectual development.'. - Ken Gergen, Mustin Professor of Psychology, Swarthmore College, Pennsylvania, and Mary Gergen, Professor of Psychology & Women's Studies, Penn State University, Delaware. 'I found Yancy and Hadley's.